EVALUATION OF ANTIDIABETIC ACTIVITY OF HYPTIS SUAVEOLENS INSTREPTOZOTOCIN INDUCED DIABETIC RATS (CAHIERS MAGELLANES-NS, 2024)
This study examines the antidiabetic potential of Hyptis suaveolens seed extract in Streptozocin (STZ)-induced diabetic rats. The experimental setup consisted of five groups to evaluate the efficacy of theextract. Wistar albino rats were categorized into five groups: Group I (normal control), Group II(diabetic control), Group III (diabetic + glibenclamide at 5 mg/kg b.wt./day orally), Group IV (diabetic+ Hyptis suaveolens seed extract at 250 mg/kg) and Group V (diabetic + Hyptis suaveolens seed extractat 500 mg/kg). The extract was administered orally for a duration of 28 days. Various parameters wereassessed, including fasting blood glucose levels, random blood glucose levels, serum insulin, HbA1c,C-peptide levels, and histopathological alterations in pancreatic tissues. The findings indicated asignificant decrease in fasting blood glucose levels in Groups III, IV, and V in comparison to the diabeticcontrol group. Notably, serum insulin and C-peptide levels were significantly elevated in Groups III,IV, and V, suggesting enhanced pancreatic beta-cell functionality. The treatment with Hyptissuaveolens seed extract in diabetic rats resulted in a marked reduction in HbA1c levels, implying animprovement in glucose metabolism and overall glycemic control. Histopathological examinationdemonstrated regeneration of pancreatic beta-cells and enhanced islet architecture in the treated groups.In conclusion, Hyptis suaveolens seed extract exhibited promising antidiabetic activity, underscoringits potential as a natural therapeutic option for diabetes management.